Eiropas Parlamenta preses relīžu par mazās uzņēmējdarbības stāvokli Eiropas Savienībā stilistiskā analīze - Griķe, Kintija (Latvijas Universitāte, 2022)
Eiropas Parlaments (EP) ir viena no svarīgākajām lēmējinstitūcijām Eiropas Savienībā. EP plenārsēdēs pieņemtie lēmumi tiek īsi apkopoti preses relīzēs. Šī pētījuma mērķis ir veikt stilistisko analīzi EP preses relīzēm par mazo uzņēmējdarbību, tā kā tai ir īpaši svarīga loma ekonomikā. Galvenās pētniecības metodes ir žanra analīze un stilistiskā analīze. Šis pētījums atklāj EP preses relīžu tipiskās leksiskās, gramatiskās un figurālās iezīmes un definē preses relīzes kā žanru. Tiek secināts, ka EP preses relīžu teikumi ir gari un pakārtoti, un tajos ir ievērojams skaits īpašvārdu, klasificējošo īpašības vārdu, viena vārda leksisko darbības vārdu, abreviatūru un metonīmiju.

The European Parliament (EP) is one of the most important decision-making bodies in the European Union. The decisions taken by the EP in plenary sessions are briefly summarised in press releases. The aim of this study is to perform a stylistic analysis of the EP press releases about small businesses since they play a particularly important role in the economy. The main research methods are genre analysis and stylistic analysis. This study discovers the typical lexical, grammatical, and figurative features of the EP press releases and defines press releases as a genre. It is concluded that the sentences in the EP press releases are lengthy and complex, and they present a considerable number of proper nouns, classifying adjectives, single-word lexical verbs, abbreviations, and metonyms.
Stylistic Analysis of the European Parliament Press Releases on the Current State of Small Business in the European Union
Keywords: Valodniecība; European Parliament; stylistic analysis; genre analysis; press release; small business